XLOC_015548 Mitigates Skeletal Muscle Atrophy via the Gadd45g/MEK/ERK Pathway and Redox Regulation - Tiantian Qi; Haotian Qin; Fei Yu; Zimeng Zhou; Yingqi Chen; Peng Liu; Hui Zeng; Jian Weng (Frontiers in Bioscience-Landmark)
Background: Skeletal muscle atrophy is a common musculoskeletal disorder that significantly reduces patient quality of life. Long non-coding RNA (lncRNA) XLOC_015548 has been identified as a pivotal regulator of C2C12 myoblast proliferation and differentiation. However, its role in mitigating denervation-induced muscle atrophy and the underlying mechanisms remain unclear. Methods: We employed lentiviral-mediated stable expression of XLOC_015548 in C2C12 myoblasts and skeletal muscle-specific XLOC_015548-edited mouse models to investigate the function of this lncRNA. Muscle atrophy models were established in vitro by glucocorticoid-induced atrophy with dexamethasone (DEX) and in vivo by sciatic nerve transection-induced denervation. The MEK inhibitor U0126 was used to assess the role of the growth arrest and DNA damage-inducible 45 gamma/mitogen-activated protein kinase kinase/extracellular signal-regulated kinase (Gadd45g/MEK/ERK) signaling pathway. Results: Overexpression of XLOC_015548 significantly activated the MEK/ERK signaling pathway (p < 0.05) by downregulating Gadd45g expression (p < 0.05) and promoting its cytoplasmic localization, thereby enhancing cell proliferation and myotube formation. Furthermore, XLOC_015548 reduced the level of reactive oxygen species (ROS) (p < 0.01), stabilized the mitochondrial membrane potential, and alleviated DEX-induced oxidative stress. These protective effects were partially reversed by U0126, confirming the involvement of the MEK/ERK pathway. Skeletal muscle-specific overexpression of XLOC_015548 in vivo significantly reduced denervation-induced muscle atrophy (q < 0.05) and increased the muscle fiber cross-sectional area. Conclusion: XLOC_015548 plays a critical role in promoting myogenic differentiation and protecting against muscle atrophy by regulating Gadd45g expression, activating the MEK/ERK signaling pathway, and reducing oxidative stress. These findings underscore the therapeutic potential of XLOC_015548 in skeletal muscle atrophy, and provide a foundation for lncRNA-based treatment strategies.